Social-Emotional Problems Among 3-Year-Olds Are Associated With an Unhealthy Lifestyle: A Population-Based Study - Eurenius, Eva; Mohamed, Amal Farah; Lindkvist, Marie; Ivarsson, Anneli; Öhlund, Inger; Vaezghasemi, Masoud (Frontiers in Public Health, 2021)
Introduction: Little attention has been paid to the association between preschool children's social-emotional problems and lifestyle at the population level. Objective: This study aimed to overcome this knowledge gap by investigating to what extent children's social-emotional problems are associated with their lifestyle and if there are any gender differences. Methods: This cross-sectional, population-based study used data from the regional Salut Register in northern Sweden, including 7,179 3-year-olds during 2014–2017. Parents responded to a questionnaire including the 36-month interval of the Ages and Stages Questionnaires: Social-Emotional (ASQ:SE) and questions regarding family and lifestyle characteristics. Single and multiple logistic regression were used to assess the association between children's social-emotional problems and multiple family lifestyle characteristics. Results: More reports of social-emotional problems were found among children who did not have parents living together or had markers of an unhealthy lifestyle. Children who ate vegetables less frequently, whose parent/-s brushed their teeth less often and did not read to them regularly were more likely to have social-emotional problems. Playing outdoors <3 h during weekdays and >1 h of sedentary screen time during weekends increased the risk of social-emotional problems among boys only, while >1 h of sedentary screen time during weekdays increased the risk among girls. When it comes to lifestyle and gender differences, a high proportion of the 3-year-olds had an unhealthy lifestyle, more so for boys than for girls. The dietary quality and tooth brushing were somewhat more adequate for the girls than for the boys, but boys spent more time playing outdoors compared to the girls. Conclusions: This study provides us with an important overview picture of the family life situation of three-year-olds, including those with social-emotional problems. Such problems were significantly associated with markers of unhealthy lifestyle, with significant gender differences. Therefore, this study suggests that in order to maintain children's social-emotional ability and support children at risk of problems, public health intervention programs should have a broader perspective on improving children's lifestyle rather than merely focusing on their social and emotional problems, and the gender differences found may be taken in account.